MEASURING THE IMPACT OF BANKING SERVICES DEVELOPMENT ON THE PERFORMANCE OF THE BANKING SYSTEM IN IRAQ - Assist prof. Dr. Fadhil Abbas Kadhim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The banking system is considered one of the most important financial institutions that have a vital role in the economy, and global progress in the field of technology and informatics has produced sophisticated scientific means to provide modern banking services, especially electronic ones, and through the experiences of other countries, the Iraqi banking system seeks to achieve the highest efficiency in its performance, By providing electronic services. Therefore, the research aims to clarify the effect of electronic banking services on the performance of the banking system, as this study came to show the impact of modern electronic services, which were considered an independent variable ((number of ATMs, number of POS points, the quarterly value of the RTGS system, and the quarterly value of the clearing) Electronic ACH), in the indicators of banking financial performance, which were represented by ((profitability, liquidity, and capital adequacy) as an applied study, and the statistical analysis tools were relied upon and the Eviews10 program was used.